Determination of the gelification kinetics of a correction gel of injection profiles by ultraviolet-visible spectroscopy. (July 2020) - Sánchez, E; Villamizar, J; Mantilla, G; Rodriguez, J; Roa, M
Abstract: Mature wells in which, for a long time, water injection has been used, as a method of recovery they reach a point where the water cut increases or remains constant. thus decreasing the recovered hydrocarbon factor; This phenomenon occurs because the water injected, has preferential recordings in the porous medium, and does not reach the hydrocarbon available in other areas of the formation, in this type of deposits the injection of polyacrylamide gels, crosslinked with acetate of chromium, these gels make a plugging, in areas of high water permeability, causing the change of path of the same, as well as move the hydrocarbon in other areas of the porous medium. At present, the kinetics of gelation of this type of substances is monitored qualitatively by means of the "Syddansk" code, which analyzes its consistency and elasticity, only by observation. Although this method is practical, it is not very descriptive and depends a lot on the opinion and criteria of the observer, being little reproducible. Given this situation, and the increase in chemical recovery projects in the country, a methodology is described that describes the moment of gelation, reproducibly and without the injection of the analyst. During the gelation process, different polyacrylamide-chromium gels were monitored in relationships used in field operations, using ultraviolet-visible spectroscopy, detecting a change in absorbances, of the spectra, which were analyzed to plant a kinetic model of gelation, in addition to generating the approach of a method, to identify the state of gelation based on the variation in absorbance.